Searches for heavy long-lived charged particles with the ATLAS detector in proton-proton collisions at $ \sqrt{s}=8 $ TeV - ATLAS collaboration (2891 authors) (2015)
Searches for heavy long-lived charged particles are performed using a data sample of 19.1 fb$^{−1}$ from proton-proton collisions at a centre-of-mass energy of $ \sqrt{s}=8 $ TeV collected by the ATLAS detector at the Large Hadron Collider. No excess is observed above the estimated background and limits are placed on the mass of long-lived particles in various supersymmetric models. Long-lived tau sleptons in models with gauge-mediated symmetry breaking are excluded up to masses between 440 and 385 GeV for tan β between 10 and 50, with a 290 GeV limit in the case where only direct tau slepton production is considered. In the context of simplified LeptoSUSY models, where sleptons are stable and have a mass of 300 GeV, squark and gluino masses are excluded up to a mass of 1500 and 1360 GeV, respectively. Directly produced charginos, in simplified models where they are nearly degenerate to the lightest neutralino, are excluded up to a mass of 620 GeV. R-hadrons, composites containing a gluino, bottom squark or top squark, are excluded up to a mass of 1270, 845 and 900 GeV, respectively, using the full detector, and up to a mass of 1260, 835 and 870 GeV using an approach disregarding information from the muon spectrometer.